Modelo de procedência para auxiliar na análise da qualidade do dado geográfico - Santos, Renata Ribeiro dos (Universidade Federal de São Carlos, 2016)
The quality of the geographic data must be a relevant concern for providers and consumers of this type of data because the manipulation and analysis of low quality geographic data may result in errors, which will be propagated through the consequent data. Thus it is important to properly document the information which allows for certifying the quality of the geographic data. In order to provide a minimum amount of metadata for such purpose, this dissertation presents an approach based on the provenance of the geographic data, which corresponds to the information about the history of such data from its origin until the processes that resulted in its current state. For this purpose, a provenance model called ProcGeo was proposed, in which it was defined a minimum amount of metadata that must be considered for the analysis of the quality of a certain geographic data. Although a few works and geographic metadata standards, such as Federal Geographic Data Committee (FGDC) and ISO 19115, consider the information about the provenance in the analysis of the quality of geographic data, it´s the opinion of the author that some metadata considered important for this purpose are not adequately contemplated. In this work, the prototype of an interface called ProcGeoInter was also implemented, aiming to guarantee the completeness and correctness in the filling out of the defined metadata in the ProcGeo model as well as the visualization of their content. The validation of the ProcGeo model and of the ProcGeoInter interface were made through tests and surveys applied to providers and consumers of geographic data. As a means of comparison, the interface for filling out and visualization of metadata available by SIG Quantum GIS (plugin Metatools) was used, which implements the FGDC geographic metadata standard. The obtained results indicated that the metadata defined in the ProcGeo model helped the geographic data provider in the description of the provenance of such data, when compared to those defined in the FGDC geographic metadata standard. Through the consumer´s focus it was possible to notice that the information filled out in the metadata defined by the ProcGeo favored the analysis of the quality of the consumed data. It was clear that both providers and consumers do not possess the habit of providing or consuming the information predicted in the FGDC and ISO 19115 geographic metadata standards.
Keywords: Procedência dos dados; Dados geográficos; Qualidade dos dados; Modelo de procedência; Metadados; Data provenance; Geographic data; Data quality; Provenance model; Metadata; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO